Beyond the Sharia-Mysticism Divide: Wali Agency and the Vernacularization of Islam in Javanese Manuscripts of the Sixteenth and Seventeenth Centuries - Djamil, Abdul; Junaidi, Akhmad Arif (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2026)
Existing scholarship on Javanese Islamic mysticism tends to portray the Javanese saints (wali) as firm proponents of Sharia who systematically opposed mystical practice. The article challenges that characterization by examining the present and development of mystical tendencies in Javanese Islamic texts from the sixteenth and seventeenth centuries. Drawing on hermeneutic and historical approaches, the study analyzes the triadic relationship between text, reader, and context, alongside the manuscript’s historical condition of production. Two primary factors are identified as shaping this phenomenon. First, the geographic relocation of political authority from the coastal, cosmopolitan Demak Sultanate to the inland agrarian polities of Pajang and Mataram created social conditions conducive to the elaboration of Manunggaling Kawulo-Gusti (the union of servant and God), a concept central to Javanese Islamic mysticism. Second, the wali functioned not merely as defenders of Sharia but as agents of religious transformation who deliberately integrated Javanese mystical frameworks with Islamic practices, recognizing that a legalistic approach was insufficient in agrarian social contexts. The article argues that the successful Islamization of Java was contingent upon the vernacularization of Islamic teaching through Javanese cultural and mystical idioms. This reframing directly contests prior scholarship that positioned the wali as opponents of mysticism.